Corporate Social Responsibility (CSR) on Company Value: The Moderating Role of Earnings Management - Junaidi, Riky Rizki; Maulana, Agus (Pusat P2M Politeknik Negeri Batam, 2025)
This study aims to analyze the effect of corporate social responsibility on firm value by considering earnings management as a moderator based on ethical theory. The research method used was content analysis of the company's annual reports to measure corporate social responsibility. Earnings management was measured using the modified Jones model, and firm value was measured by Tobin's Q. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange in the period 2020-2022. Data was collected from the company's annual report and the company's website, while financial data was taken from the Thomson Reuters Eikon database. This study found evidence that CSR has a significant negative effect on firm value and earnings management strengthens the effect of CSR on firm value. The results of this study have implications in providing better guidance for companies in implementing CSR, taking into account the importance of financial transparency and accountability, as well as reducing the risks associated with earnings manipulation.